Fracture energy of nano- and micro-silica particle-filled epoxy composites. (12th July 2011) - Adachi, Tadaharu; Imai, Yoshinori; Higuchi, Masahiro
The effects of particle size on the surface energy of the fracture surface and elastic moduli of nano- and micro-spherical silica-particle-filled epoxy composites were investigated experimentally. The Young's modulus and shear modulus of the composites agreed well with the results evaluated by Lewis and Nielsen's equation and were shown to be dependent on only the volume fraction of the particle. Surface energies of the fracture surface were evaluated from the critical energy release rates and the surface areas including the unevenness. The surface energies were shown to be constant regardless of the volume fraction of the particle.